Child health promotion from the perspective of family health strategy nurses - Alcantara, Aline Biondo [UNESP]; Lima, Lilian de [UNESP]; Duarte, Marli Teresinha Cassamassimo [UNESP]; Parada, Cristina Maria Garcia de Lima [UNESP]; Tonete, Vera Lúcia Pamplona [UNESP] (FapUNIFESP (SciELO), 2022)
OBJECTIVE: To apprehend nurses' conceptions and experiences about actions of child health promotion in family health units. METHODS: Exploratory study, with thematic content analysis of statements, obtained through semi-structured interviews with 11 nurses from a municipality in São Paulo. RESULTS: Three thematic categories emerged on child health promotion actions: they must be contextualized, provide for comprehensive care, and aim at self-care; they are carried out through health guidelines shared by professionals with children and their families, inside and outside the health units; present challenges to be overcome by health services, such as lack of involvement and appreciation of the family regarding child follow-up. CONCLUSIONS: The concepts apprehended approached the premises of official documents on health promotion; however, practical experiences included difficulties related to the life contexts of children, their families and health services, compromising the achievement of comprehensive care.